Validity and Development of Anyflip Application-Based Electronic Module in View of Student Learning Outcomes - Nanang Khuzaini; Nuryadi; M Farid Nasrulloh (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to make mathematics learning media in the form of electronic modules using the Anyflip application which is of good quality and appropriate for use in learning mathematics. The anyflip application is a software developer for creating electronic modules. The quality criteria used as a reference in this study are Nieveen's criteria, namely validity, practicality, and effectiveness. The design of this research is research development (Research Development). In carrying out this research, the stages of developing mathematics learning media in the form of electronic modules using the Anyflip application use a development model adapted from the Borg and Gall development model. The development stages carried out were (1) Preliminary study, (2) Planning, (3) Draft development, (4) Limited field trial, (5) Product revision, (6) Small group trial, (7) Test field trials, and (8) Distribution and use. Product validity was obtained from the validation of material experts and learning device experts to assess the products being developed. The research instruments used were material expert validation sheets and learning device expert validation sheets. This research produces an electronic module for learning mathematics using the Anyflip application that is of good quality and feasible. The results of this study indicate that the developed electronic module for learning mathematics is valid based on the results of assessments from material experts and learning device experts.